Descriptive Analysis of Acceptance by Prescribers and Economic Benefit of Pharmacist Recommended Interventions in a Critical Care Unit - YoonJung Lee; Lana Gettman (University of Minnesota Libraries Publishing, 2018)
Background: Pharmacist clinical intervention is defined as the action that identifies and prevents medication-related problems and optimizes patient's medication therapy in cooperation with other healthcare professionals. Types of clinical interventions may vary, but each is patient specific. Few studies have focused on clinical pharmacists interventions in a critical care setting at a rural hospital. Objectives: The purpose of this study was to assess physician acceptance rate of pharmacist-recommended interventions in the critical care unit (CCU) at a rural hospital over five years and to evaluate the economic benefit of accepted pharmacist-recommended interventions over a one-year time period. Methods: This study was a retrospective chart review over a five-year time period. Each intervention was categorized and analyzed for acceptance or non-acceptance by the treating physician. Evaluation of economic benefit, cost saving and cost avoidance, for a one-year time period was performed. Results: A total of 1275 interventions were documented during study period. The average acceptance rate for documented interventions was 56%. The acceptance rate by physicians increased over the study period; with the acceptance rate in 2013 being statistically significantly higher than any other years. The overall cost saving for selected interventions was $432 for the one year. The overall cost avoidance of all accepted interventions for the one year was $453,339.36-$468,327.62. Conclusion: Clinical pharmacists provide various types of interventions to improve patient care. The analysis of potential cost saving and cost avoidance of selected interventions illustrated a positive economic outcome.   Conflict of Interest "We declare no conflicts of interest or financial interests that the authors or members of their immediate families have in any product or service discussed in the manuscript, including grants (pending or received), employment, gifts, stock holdings or options, honoraria, consultancies, expert testimony, patents and royalties". Treatment of Human Subjects: IRB exemption granted   Type: Original Research